VALIDITY AND PRACTICALITY OF E-COMIC BASED ON CHARACTER EDUCATION TO PREVENT JUVENILE DELINQUENCY IN STUDENTS - Nurzena; Rizki Amelia; Emilia Susanti; Iqbal Miftakhul Mujtahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
One of method For prevent mischief teenager is with give education Character . Education character help student understand principles character in a way comprehensive And increase awareness they about danger mischief Study This is study Research and Development which aims develop E-COMIC Media Based Education Character For Prevent Delinquency in Pekanbaru . Research This using the ADDIE model, which was developed by Dick Walter and Lou Carey. On stage analysis , there are 8 lecturers , 5 teachers who are certified as e-comic media validators, 97 students , and 77 students participated as respondents . Based on results study development that has been done Product development in the form of E-Comic based Education Character has fulfil criteria validity by 91% with “ Very Valid” criteria . practicality by 83% with “ Practical ” category and effective. This study aligns with the findings of Oktaviana et al. (2024), who used the ADDIE model for developing e-comic media focused on global diversity character education. Similarly, Suwanda et al. (2024) found that digital comics based on character education achieved high validation scores from both material and media experts, reinforcing the suitability of the ADDIE framework.